Ischial Form as an Indicator of Bipedal Kinematics in Early Hominins: A Test Using Extant Anthropoids. Issue 5 (May 2017) - Lewton, Kristi L.; Scott, Jeremiah E.
ABSTRACT: Human ischia contrast with those of great apes in being craniocaudally short and dorsally projecting. This configuration is thought to facilitate greater hip extension in humans during bipedal locomotion. This link has been used to infer kinematics in early hominins, but the consequences of variation in ischial configuration for gait remain uncertain. Kinematic data for a limited sample of extant nonhuman primates demonstrate that there is variation in hip extension in these taxa during bipedal behaviors—specifically, Hylobates and Ateles are capable of greater extension than Pan and Macaca . In this study, we tested the hypothesis that ischial length and orientation are functionally linked with hip extension during bipedalism among these taxa. As expected, humans have the shortest ischia, followed by gibbons, spider monkeys, chimpanzees, and macaques. Our predictions for ischial orientation are not supported, however: macaques, gibbons, and spider monkeys do not vary in this trait, and they have ischia that are less dorsally angled than that of the chimpanzee. The results for ischium length provide limited support for the idea that the early hominin Ardipithecus ramidus, with its long, caudally oriented ischium was not capable of humanlike extended‐hip bipedalism, and that the ischial shortening observed in post‐ Ardipithecus hominins reflects a shift toward a more humanlike gait. In contrast, while our results do not necessarily refute a link between ischial orientation and hip extension in hominins, they do not provide comparative support, making changes in ischial orientation in this part of the fossil record more difficult to interpret. Anat Rec, 300:845–858, 2017. © 2017 Wiley Periodicals, Inc.